Critical Voices and the Burden of Free Expression among Arab Intellectuals - Yoyo, Yoyo (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
This paper analyzes the freedom of expression challenge (taâ€™bÄ«r al-hurriyyah) through Arab intellectual experiences. Although freedom of expression has doctrinal support and historical factual expertise in Islam, it is still challenging to find its actual implementation within the Arab world, especially in Arab countries with authoritarian systems. Therefore, the paper begins by exploring several examples of intimidation experienced by Arab intellectuals as the consequences of their critical ideas and voices. Specifically, the paper examines freedom of expression among Arab scholars in Syrian as an authoritarian state. The failure of the Arab Spring made it more difficult for freedom of expression to find its free space. As a qualitative study, data was collected by gathering essential information from journals, books, and online websites. The data were then analyzed through critical reading based on formulated research questions. The paper concluded that freedom of expression has its historical doctrine in Arab-Islam. However, this moral doctrine did not lead to absolute freedom of expression. It is proved that most Arab intellectuals experienced bitter life due to their critical voices. In the Syrian context, Arab intellectuals are divided between those who support the regime and maintain opposition to the ruling government. However, the opposition keeps conducting the reform in silence since the voices and protests will lead them to exile or death. Due to this polarization, critical voices in Syria have not successfully become a powerful movement.Â